High Magnitude of Social Anxiety Disorder in School Adolescents. (16th February 2017) - Mekuria, Kindie; Mulat, Haregwoin; Derajew, Habtamu; Mekonen, Tesfa; Fekadu, Wubalem; Belete, Amsalu; Yimer, Solomon; Legas, Getasew; Menberu, Melak; Getnet, Asmamaw; Kibret, Simegnew
Abstract : Introduction. Social phobia is the most prevalent and chronic type of anxiety disorder worldwide and it affects occupational, educational, and social affairs of the individual. Social phobia is also known for its association with depression and substance use disorder. Objective. The aim of this study was to assess the prevalence and associated factors of social phobia among high school students in Ethiopia. Methods. Cross-sectional study was conducted among 386 randomly selected students. Data were collected using pretested and self-administered questionnaire. Social phobia was assessed by using Social Phobia Inventory (SPIN). Logistic regression was used to analyze the data with 95% confidence interval and variables withp value less than 0.05 were considered as statistically significant. Results. From 386 study participants, 106 (27.5%) of them were positive for social phobia. Being female (AOR = 3.1; 95% CI: 1.82–5.27), current alcohol drinking (AOR = 1.75; 95% CI: 1.03–2.98), poor social support (AOR = 2.40; 95% CI: 1.17–4.92), and living with single parent (AOR = 5.72; 95% CI: 2.98–10.99) were significantly associated with social phobia. Conclusion. The proportion of social phobia was higher compared to previous evidences. School-based youth-friendly mental health services might be helpful to tackle this problem.